Dominance of Zygosaccharomyces and shifts in bacterial pathways: Effects of antimicrobials on composition and diversity of the Ceratitis capitata bacterial and fungal microbiome - Maria Cecilia Rasuk; Alfonsina Palladini; Andrea Moyano; Viviana Díaz; Antonella Giudice; Gisela Castillo; Solana Abraham; Juan Rull; Anja Poehlein; Rolf Daniel; Julian Rafael Dib (PLoS ONE, 2025)
The Mediterranean fruit fly ( Ceratitis capitata Wied.) is an agricultural pest of significant economic importance. This species has been globally managed using the Sterile Insect Technique (SIT). Insects, including tephritid flies, harbor a diverse gut microbiota that plays critical roles in their physiology, behavior, and overall fitness, suggesting that microbial communities may profoundly influence the biology of this pest. The aim of this study was to characterize the fungal and bacterial gut microbial communities of C. capitata from Tucumán, Argentina, and to assess their response to antimicrobial treatment using amplicon-based 16S rRNA gene and ITS region sequencing. Both control and treated flies were dominated by Proteobacteria (bacteria) and Zygosaccharomyces (fungi). Antimicrobial treatment induced significant shifts in bacterial and fungal composition, reducing diversity and altering gut community structure. Untreated flies exhibited a diverse and structured bacterial gut community dominated by the family Enterobacteriaceae, while antibiotic-treated communities were dominated by Rhizobiaceae. Despite these shifts, fungal communities in both treated and untreated groups were consistently dominated by the genus Zygosaccharomyces . Functional predictions revealed notable changes in metabolic pathways following antibiotic treatment, including increased gene abundance for ABC transporters and the phosphotransferase system, and decreased representation of genes involved in antibiotic biosynthesis and two-component systems. These results indicate significant alterations in bacterial metabolism and stress response mechanisms induced by the treatment. Such changes may help explain the underperformance of irradiated, mass-reared males within the context of SIT. This study provides new insights into the structural and functional dynamics of the C. capitata gut microbiome under disturbance. These findings have implications for understanding the ecological roles of microbial communities in this pest and their potential impact on fly health and fitness. Identification of dominant gut bacterial and fungal groups may support the development of probiotic diets, enhancing the efficiency of SIT application.